2016
DOI: 10.4067/s0718-915x2016000100006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adhesive replacement with cement mortar on NSM strengthened RC Beam

Abstract: This paper presents the experimental behavior of reinforcement concrete beams strengthened with near surface mounted (NSM) steel bar. Several researchers have used NSM fiber reinforced polymer (FPR) bar or strip for strengthening reinforced concrete beams. Though FRP has a number advantages like high strength, light weight and corrosion resistance it doesn't show any ductile behavior, still highly expensive and not easily available in market. On the other hand, steel bar is less expensive, readily available in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Organic resins such as epoxy and vinyl esters are widely used as bonding materials in FRP strengthening of concrete members, however, inorganic resins possess numerous advantages over the organic resins; including: (a) better resistance against high temperatures, (b) improved UV resistance, (c) handling and use is simpler as the inorganic resins are water-based, (d) they emit no toxic smells during strengthening, and (e) comparable chemical bonding with concrete. When properly designed, it is possible to replace organic resins with inorganic ones for most strengthening applications [19][20][21][22][23][24][25]. Rahman et al [19] studied the efficiency of cement mortar and epoxy resin as a bonding material for NSM strengthening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic resins such as epoxy and vinyl esters are widely used as bonding materials in FRP strengthening of concrete members, however, inorganic resins possess numerous advantages over the organic resins; including: (a) better resistance against high temperatures, (b) improved UV resistance, (c) handling and use is simpler as the inorganic resins are water-based, (d) they emit no toxic smells during strengthening, and (e) comparable chemical bonding with concrete. When properly designed, it is possible to replace organic resins with inorganic ones for most strengthening applications [19][20][21][22][23][24][25]. Rahman et al [19] studied the efficiency of cement mortar and epoxy resin as a bonding material for NSM strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…When properly designed, it is possible to replace organic resins with inorganic ones for most strengthening applications [19][20][21][22][23][24][25]. Rahman et al [19] studied the efficiency of cement mortar and epoxy resin as a bonding material for NSM strengthening. They found that the replacement of 50% epoxy with mortar resulted in better performance without altering the flexure dominant failure.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental performance of concrete beams reinforced with a steel bar to discuss failure in the load, the regime of failure, deflection, and strain performance. The study reveals that proposed techniques most cost-effective reinforcement to increase the bending efficiency of RC beams [2].The loading has been implemented through a motion management regime. The four samples are utilized for experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reinforced polymer (FRP) composites have been increasingly used in concrete structures in recent years because of their corrosion resistance, low weight, high tensile strength and large strain (Rahman, Jumat, Hosen, & Islam, 2016). Shear strengthening of beams can be implemented quickly by external carbon fibre-reinforced polymer (CFRP).…”
Section: Introductionmentioning
confidence: 99%